Studi Kebijakan Penguatan Program Perumahan Dalam Mewujudkan Kesejahteraan Bagi Pegawai Negeri Pada Polri: Studi Kebijakan Penguatan Program Perumahan Dalam Mewujudkan Kesejahteraan Bagi Pegawai Negeri Pada Polri - Aziz, M Asrul; Suprapto, Heri (Jurnal Litbang Polri, 2023)
The house as one of the basic human needs, ideally should be owned by every family, especially for people with low incomes and for people who live in densely populated areas in urban areas. The state is also responsible for providing and facilitating the acquisition of houses for the community through the implementation of housing and residential areas, including for Civil Servants at the Indonesian National Police (PNPP). The research that has been carried out by the Indonesian National Police Research and Development Center aims to: mapping the availability and potential of housing availability for PNPP along with the physical, environmental and socio-geographic characteristics of the building, map regulations, policies and other provisions related to PNPP housing tenure, get an overview of the willingness to buy the right one. obtained through shopping behavior, investment, characteristics of interest, inclination, and ability to buy, as well as designing strategic formulations of policies for strengthening housing programs (official houses and ownership houses for PNPP). In this study, data collection was carried out using a questionnaire and Focus Group Discussion (FGD), with a sample location of 12 Regional Police of the Republic of Indonesia. The conclusion of the research is that the Indonesian National Police Chief's program to fulfill PNPP needs with a target of 100,000 houses, which is part of the Indonesian National Police Chief's 100-day program, shows that the Indonesian National Police Chief's determination to meet the welfare of members/PNPP through housing must get the attention of all head of work unit from all levels of the Police. Private housing for PNPP is very important and strategic to support the duties of the Police wherever they are assigned to ensure work professionalism and are active in maintaining security and social order in Indonesia